PENGARUH MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN PENALARAN MATEMATIS PADA SISWA SD NEGERI PAKULONAN 01 KELAS IV - Fadlatul Ramdhan; Mawardi; E. Sumadiningrat (STKIP Subang, 2023)
This research was conducted because of the symptoms of low levels of independent learning and student learning motivation. This is because there are still many students who only memorize mathematical formulas but do not understand mathematical concepts. This study aims to determine the effect of learning motivation and learning independence on mathematical reasoning abilities in elementary school students. The analysis used in this survey method is multiple regression analysis. The reachable population in this study were all fourth graders of Pakulonan 01 Public Elementary School, South Tangerang City. The sample studied was 30 students consisting of grades IV A and IV C. Data collection techniques used test instruments and questionnaires. The hypothesis testing shows that: (1) There is a significant influence between learning motivation on the mathematical reasoning abilities of elementary school students by 17.1%. (2) There is a significant influence between learning independence on mathematical reasoning abilities in elementary students of 16.2%. (3) There is a significant influence between the influence of learning motivation and learning independence on the mathematical reasoning abilities of elementary students by 14.4%.